Remote Working and Using the Services of the 15-Minute City. An Analytical Model Based on Data Collected in Milan - Giampaolo Nuvolati; Anne-Iris Romens (Sociologica)
The essay aims to explore the extent to which remote work fosters the 15-Minute City by increasing the use of local services. It proposes a model of analysis to study the impact of remote work on the use of services that focuses on two variables: a) the use of services in the neighbourhood; and b) the frequency with which workers perform their job remotely. Then, the contribution tests the model by referring to empirical data collected in the Milan area that consisted of a Survey developed in 2022, after the pandemic, with 285 remote workers of the quaternary sector. Our analysis highlights that remote work is mainly being performed at home and fosters the use of supply and leisure services in the neighbourhood, which ultimately encourages the development of the 15-Minute City. Although a high frequency of remote work relates to a higher propensity to use neighbourhood services, a significant group of full-time remote workers do not use services closer to their homes, which underlines the need to take into account other variables to understand the choice to use proximity services or not.